2009
DOI: 10.1088/1674-0068/22/04/339-345
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron-Radiation Photoemission Study of Growth and Stability of Au Clusters on Rutile TiO2(110)-1 1

Abstract: The growth and thermal stability of Au clusters on a partially-reduced rutile TiO2(110)-1 1 surface were investigated by high-resolution photoelectron spectroscopy using synchrotron-radiation-light. The valence-band photoelectron spectroscopy results demonstrate that the Ti3+3d feature attenuates quickly with the initial deposition of Au clusters, implying that Au clusters nucleate at the oxygen vacancy sites. The Au4f core-level photoelectron spectroscopy results directly prove the existence of charge transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…12,13 Au nanoparticles prepared by Au vapor deposition were observed to preferentially nucleate at surface oxygen vacancy sites of the reduced rutile TiO 2 (110) surface with charge transfer from the substrate to the Au clusters, and such a charge transfer effect strongly modulates the electronic structure of supported Au nanoparticles and greatly enhances their stability. 14,15 It was also reported that an oxidized rutile TiO 2 (110) surface with oxygen adatoms adheres Au clusters more strongly than a reduced rutile TiO 2 (110) surface with surface oxygen vacancy sites. 16 However, studies of growth and structures of Au nanoparticles on other TiO 2 single-crystal surfaces are quite limited, although the TiO 2 surface structures strongly depend on the crystal planes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…12,13 Au nanoparticles prepared by Au vapor deposition were observed to preferentially nucleate at surface oxygen vacancy sites of the reduced rutile TiO 2 (110) surface with charge transfer from the substrate to the Au clusters, and such a charge transfer effect strongly modulates the electronic structure of supported Au nanoparticles and greatly enhances their stability. 14,15 It was also reported that an oxidized rutile TiO 2 (110) surface with oxygen adatoms adheres Au clusters more strongly than a reduced rutile TiO 2 (110) surface with surface oxygen vacancy sites. 16 However, studies of growth and structures of Au nanoparticles on other TiO 2 single-crystal surfaces are quite limited, although the TiO 2 surface structures strongly depend on the crystal planes.…”
Section: Introductionmentioning
confidence: 97%
“…Au/TiO 2 catalysts are one of the earliest and most extensively studied systems of Au catalysis. A volcano-shape dependence of their catalytic activity in low-temperature CO oxidation on the Au particle size has inspired many fundamental studies to understand the growth and structures of Au nanoparticles on TiO 2 that mostly use a rutile TiO 2 (110) single crystal as a model surface for TiO 2 . The catalytic activity of Au nanoparticles supported on the rutile TiO 2 (110) surface also exhibited a volcano shape-dependent catalytic activity in low-temperature CO oxidation on the Au particle size. , Au nanoparticles prepared by Au vapor deposition were observed to preferentially nucleate at surface oxygen vacancy sites of the reduced rutile TiO 2 (110) surface with charge transfer from the substrate to the Au clusters, and such a charge transfer effect strongly modulates the electronic structure of supported Au nanoparticles and greatly enhances their stability. , It was also reported that an oxidized rutile TiO 2 (110) surface with oxygen adatoms adheres Au clusters more strongly than a reduced rutile TiO 2 (110) surface with surface oxygen vacancy sites . However, studies of growth and structures of Au nanoparticles on other TiO 2 single-crystal surfaces are quite limited, although the TiO 2 surface structures strongly depend on the crystal planes.…”
Section: Introductionmentioning
confidence: 99%
“…For scattering from metal nanoclusters adsorbed on insulating substrates, it has been shown that the NF directly correlates with the size of the nanoclusters. , Small clusters have quantum-confined electronic states, and the clusters are generally thought to be negatively charged, , so that electrons from these filled states efficiently neutralize the scattered alkali ions. In contrast, solid Au has a rather large work function compared to the Na and K ionization energies, so that the neutralization probability of Na + and K + in scattering from bulk Au is near zero. , Thus, the NF decreases as more Au is deposited and the size of the clusters increases so that the Au becomes more bulk-like.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report from our group 22 agrees with work from the literature in that the clusters contain positively charged Au atoms, [55][56][57][58][59] although others have concluded that the clusters are overall negatively charged. [60][61][62][63] It was calculated from density functional theory (DFT) that the edge atoms of a nanocluster are the ones that are positively charged 59,64 and upward pointing dipoles are thus created at those sites. These upward pointing dipoles create a lower LEP, as with alkali adatoms, which raises the NF of the projectiles scattered from the edge atoms.…”
Section: Discussionmentioning
confidence: 99%